Kajian Yuridis Penerapan Struktur Skala Upah Bagi Perusahaan Berdasarkan Hukum Ketenagakerjaan - Nienne Aridayanthi Hainun (Journal of Contemporary Law Studies, 2026)
The wage structure and wage scale are essential instruments within the national wage system to ensure fairness, legal certainty, and the protection of workers’ rights. Nevertheless, in practice, some companies still fail to establish these mechanisms. This study aims to examine the regulation of wage structures and wage scales under Indonesian labor law and to analyze the legal consequences for companies that do not comply with this obligation. The research employs a normative juridical method using statutory, conceptual, and analytical approaches. Data were obtained through a literature review of primary, secondary, and tertiary legal materials, which were analyzed using a descriptive analytical technique. The findings demonstrate that the obligation to formulate and disclose wage structures and wage scales to workers is explicitly regulated under Indonesian labor law, particularly Article 92 of Law Number 6 of 2023 on Job Creation and Article 21 of Government Regulation Number 36 of 2021 on Wages, as amended by Government Regulation Number 51 of 2023 and Government Regulation Number 49 of 2025. These provisions require all employers, without exception, to establish wage structures and wage scales based on principles of fairness, company capability, and productivity, while considering job classification, length of service, education, and competence.